2018
DOI: 10.1007/s12275-018-8144-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of IE62 mutations found in Varicella-Zoster virus vaccine strains for transactivation activity

Abstract: Live attenuated vaccine strains have been developed for Varicella-Zoster virus (VZV). Compared to clinically isolated strains, the vaccine strains contain several non-synonymous mutations in open reading frames (ORFs) 0, 6, 31, 39, 55, 62, and 64. In particular, ORF62, encoding an immediate-early (IE) 62 protein that acts as a transactivator for viral gene expression, contains six non-synonymous mutations, but whether these mutations affect transactivation activity of IE62 is not understood. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To date, limited data has been published regarding the Korean vaccine strain SuduVax [10,11,31]. The comparative genome sequencing of clinical and vaccine strains of VZV revealed 24 vaccine-specific SNP sites that we previously detected in high passage clinical strains, such as Ellen, 32p72, YC01, and YC02 [20].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…To date, limited data has been published regarding the Korean vaccine strain SuduVax [10,11,31]. The comparative genome sequencing of clinical and vaccine strains of VZV revealed 24 vaccine-specific SNP sites that we previously detected in high passage clinical strains, such as Ellen, 32p72, YC01, and YC02 [20].…”
Section: Discussionmentioning
confidence: 87%
“…Given that ORF62 encodes for immediate early protein 62, which enables the activation of the majority of VZV promoters during lytic infection, ORF62 mutations may regulate the expression of many VZV genes. In fact, Ko et al previously reported that IE62 from SuduVax strains showed significantly reduced transactivation activity for the ORF4, ORF28, ORF29, and ORF68 promoters compared with wildtype IE62 from wildtype VZV strains [31]. Furthermore, IE62 suppresses innate immunity by inhibiting IRF expression as well as blocking the phosphorylation of IRF3 and inhibiting IFN production [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORF62 is the gene that in the vOka strain contains the major number of SNPs compared to pOka, of which four are highly fixed, with two of them causing R958G and S628G substitutions in two highly conserved regions of the ORF62 gene [ 106 ]. It also appears that vOka IE62 induces a decreased level of gene transcription compared to pOka IE62 [ 107 ]. All in all, the current available evidence suggests that IE62 may play an important role in the skin attenuation of the VZV vaccine and studies aimed at elucidating these mechanisms are underway.…”
Section: Vzv Vaccine and Skinmentioning
confidence: 99%